THE EFFECT OF SOCIAL SUPPORT AND ACADEMIC RESILIENCE ON STUDENTS' PSYCHOLOGICAL WELL-BEING - Ginting, Selly Noviana; Suharsono, M; Eriany, RA. Praharesti (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Living a life in a foreign land is not easy, because you have to be far from your nuclear family. However, to achieve a better life, many people migrate to get higher education outside the region. Migrant students will certainly experience a lot of complex mental turmoil. Therefore, this study aims to determine the effect of social support and academic resilience on psychological well-being in migrant students from outside Java. The method used is quantitative multiple linear regression and simple linear regression. The number of participants was 240 migrant students from outside Java using accidental sampling techniques. Measurements used Oslo Social Support (OSSS-13), Academic Resilience Scale (ARS-30), and Ryff's Psychological Well-Being Scale (RPWBS). The results of the study showed that social support and academic resilience together did not affect psychological well-being (F = 1.796 and sig. = 0.168; p> 0.05). Specifically, social support does not affect psychological well-being (t = -1.716 and sig. = 0.087; p>0.05). Likewise, academic resilience does not affect psychological well-being (t = -0.962 and sig. = 0.337; p>0.05). These results indicate that social support and resilience are not the main factors that influence the achievement of psychological well-being of students from outside Java.